2015
DOI: 10.1016/j.optmat.2014.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and optical characterization of Cu2ZnGeSe4 thin films

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: substrates at a substrate temperature of 300 and 420 K. CZGSe films were characterized by Xray diffraction (XRD), energy dispersive X-ray spectroscopy, scanning electron microscopy and by the method of normal incidence transmittance and reflectance. XRD studies reveal an improved crystallinity of the polycrystalline CZGSe films with tetragonal structure when the substrate temperature was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…5,[7][8][9] In addition, the partial substitution of Sn by Ge increases the bandgap of the kesterite semiconductor material enabling the creation of a graded bandgap through the development of indepth compositional engineering strategies. 10,11 On the other hand, the total substitution of Sn by Ge (CZGSSe) appears as an even more promising approach since, in addition to completely avoiding Sn-related issues, the wider bandgap of the material ($1.5 eV for CZGSe and $2.2 eV for CZGS) 12,13 opens the door to semi-transparent, tandem and photocatalytic water splitting applications. Signicant advances have been made in the last years in pure Ge kesterite solar cells leading to CZGSe devices with efficiencies of up to 8.5%.…”
Section: Introductionmentioning
confidence: 99%
“…5,[7][8][9] In addition, the partial substitution of Sn by Ge increases the bandgap of the kesterite semiconductor material enabling the creation of a graded bandgap through the development of indepth compositional engineering strategies. 10,11 On the other hand, the total substitution of Sn by Ge (CZGSSe) appears as an even more promising approach since, in addition to completely avoiding Sn-related issues, the wider bandgap of the material ($1.5 eV for CZGSe and $2.2 eV for CZGS) 12,13 opens the door to semi-transparent, tandem and photocatalytic water splitting applications. Signicant advances have been made in the last years in pure Ge kesterite solar cells leading to CZGSe devices with efficiencies of up to 8.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Some preparation details of crystal and thin films, as well as structural studies were published in [11][12][13][14]. The optical properties were studied by means of transmittance [13,[15][16][17][18], reflectance [13,[15][16][17][18][19], photoluminescence [10,15,20,21] and ellypsometry [22][23][24] measurements. The room temperature electrical properties [13,17], as well as the temperature dependence of resistivity in CZGeSe single crystals [25] were investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…This synthesized CZGeSe absorber exhibits an optical bandgap of 1.5 eV, which is very near to optimal bandgap of solar energy harvesting devices. Levcenko et al observed that the optical bandgap of ion beam‐sputtered CZGeSe thin film decreased from 1.52 to 1.17 eV as the substrate temperature increased from 300 to 420 K. [ 90 ] The possible existence of the secondary phases like Cu 2 GeSe 3 and Cu 1.8 Se with E g of 0.77 [ 91 ] and 1.23 eV, [ 92 ] respectively, might be responsible for the reduction of the derived bandgap values for CZGeSe. Disordered structure of CZGSe film same as Sn‐based kesterites (Cu 2 ZnSnS 4 ) may also be responsible for this deviation of bandgap values from the derived range of values of 1.29–1.63 eV for a single‐crystal CZGeSe thin film.…”
Section: Substitution Of Cations In Cztsmentioning
confidence: 99%